2005
DOI: 10.2337/diabetes.54.9.2744
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mouse Overexpressing Syntaxin-1A as a Diabetes Model

Abstract: fasting hyperglycemia and a more sustained elevation of plasma glucose levels after an intraperitoneal glucose tolerance test, with correspondingly reduced plasma insulin levels. Surprisingly, ␤-cells from the STX-1A male mice also exhibited abnormal insulin tolerance. To unequivocally determine the ␤-cell secretory defects, we used single-cell analyses of exocytosis by patch clamp membrane capacitance measurements and ion channel recordings. Depolarization-evoked membrane capacitance increases were reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
2
43
1
Order By: Relevance
“…Reduced insulin release has been commonly linked to defective exocytosis. Stxbp1 positively regulates insulin secretion, and it has been reported to be reduced in the islets of both T2D patients and GK rats (Zhang et al 2002, Lam et al 2005, Andersson et al 2012. Our results indicated that the expression levels of miR-218 and miR-322 were raised in mouse islets exposed to high levels of glucose for a long period (72 h), which is followed by the sharp decrease in expression of Stxbp1 and the blocking of insulin secretion.…”
Section: Figuresupporting
confidence: 50%
“…Reduced insulin release has been commonly linked to defective exocytosis. Stxbp1 positively regulates insulin secretion, and it has been reported to be reduced in the islets of both T2D patients and GK rats (Zhang et al 2002, Lam et al 2005, Andersson et al 2012. Our results indicated that the expression levels of miR-218 and miR-322 were raised in mouse islets exposed to high levels of glucose for a long period (72 h), which is followed by the sharp decrease in expression of Stxbp1 and the blocking of insulin secretion.…”
Section: Figuresupporting
confidence: 50%
“…Our previous report on syntaxin-1A-overexpressing mice showed that a moderate increase of ϳ30% of islet syntaxin-1A levels was sufficient to cause hyperglycemia from reduction in ␤-cell insulin exocytosis and inhibition of L-type Ca 2ϩ current density (49). However, there was no effect on K ATP or Kv2.1 channels, suggesting that these distinct components of the insulin secretory process exhibit differing sensitivity to syntaxin-1A modulation.…”
Section: Discussionmentioning
confidence: 85%
“…Both Stx1a knock out -and Stx1a transgenic mice display a reduced insulin release and an impaired glucose homeostasis, possibly via an aberrant regulation of pancreatic b-cell ion channels. The genetic alteration of STX1A levels might also contribute to impaired glucose metabolism, which occurs with increased incidence in adults with WBS [23,163,164]. In cognitive functional test, Stx1a knock out mice demonstrated an increased conditioned fear memory lacking any other difference in appearance compared with control littermate [165].…”
Section: The Single Copy Gene Part Of the Wbs Regionmentioning
confidence: 99%